The Relationship of Independent Learning with Student Learning Outcomes in Electrical Engineering Drawing Subject Class X of Electrical Installation at Vocational High School 2 Manado - Handy Hepsiba Sudarsono; Djami Olii; Calvin. E. J. Mamahit (Journal on Education, 2024)
This research aims to determine: the relationship between independent learning and learning outcomes in the electrical engineering drawing subject of the TITL Department at public vocational secondary schools 2 Manado. This study uses a quantitative approach. The type of research is correlational. This research is research involving a population with a population of 24 students. Data was collected using a research instrument in the form of a questionnaire. Of the 22 questions tested, there were 20 valid questions with a reliability value of 0.944. The data analysis technique used is Pearson product moment correlation. The results of the research show that: (1) the average/mean learning independence of class Negeri 2 Manado is 75.74 or in the High category, and (3) there is a positive and significant relationship between learning independence and learning outcomes in the electrical engineering drawing subject of the TITL Department at public vocational secondary schools 2 Manado. This is shown by the value of r calculated being greater than r table (0.985 > 0.349) and a significance value of 0.000, which means less than 0.05 (0.000<0.05). Thus, it can be concluded that there is a relationship between learning independence and learning outcomes in the electrical engineering drawing subject of the electrical engineering department, State Vocational High School 2 Manado